PROBLEMATIKA PENEGAKAN HUKUM TERHADAP PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI LUAR NEGERI: ANTARA REGULASI DAN REALITAS - Nabila, Sitti (RIO LAW JURNAL, 2025)
The enforcement of national law in protecting the rights of Indonesian Migrant Workers (PMI) based on Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers is a crucial effort to ensure comprehensive protection for PMI. Although this law introduces a new paradigm emphasizing the state's role throughout the migration process, its implementation still faces serious challenges from institutional weaknesses, inter-agency coordination, and limited capacity of local governments and overseas representatives. Structural obstacles such as the absence of strong bilateral agreements and differing legal systems in host countries further weaken PMI protection. Cultural factors, including discrimination, language barriers, and workers’ reluctance to report abuses, also impede access to justice. This article analyzes the effectiveness of national law enforcement and the structural and cultural barriers faced in implementing PMI protection, and offers recommendations for institutional strengthening, integrated digital systems, and international cooperation as solutions to improve legal protection for PMI in practice.Keywords: Law enforcement, Indonesian Migrant Workers, Legal protection